Historical Reflection on the Imperative of Security Sector Reform (SSR) in A Democratic Society - Iyanda Kamoru Ahmed (International Journal of Trends in Humanities, 2024)
The end of Cold War heralded “Hot Peace” into the international system. Before then, people thought that the conclusion of the Cold War would bring about a lasting peace on a global scale. However, this noble aspiration was not 1a be s- September-il, amply and—brutally demonstrated besides, the increasing wave of terrorism. Global democratization efforts brought about the end of the Cold War. People all across the world took advantage of the political space that was created to assert their individual and communal rights, sometimes using violence, as a result of the intentional action's unforeseen effects. In hindsight, the use of the state's brutal coercive power to suppress people and groups thought to hold opposing views, regardless of how beneficial those viewpoints could be, is what ultimately kept the Cold War going. However, democratization eliminated the cap. When the development donor partners and multilateral institutions realized how grave a threat this "healthy" development or situation was to democratization, they had to abandon their old support model and demand on security sector reform. Practically speaking, democracy and reform in the security sector reinforce each other. We will examine whether or not this link is true in this work and utilize the results to provide a paradigm that would support it.
Keywords: Cold war; coercive power; democratic society; democratisation; global terrorism; multilateral institutions